Distant parts and the whole world: Intertextuality Pseudoworks in the Abbé Prévost’s Voyages de Robert Lade - Baker, Benjamin H. (Cadernos de Literatura Comparada, 2014)
To reach a better understanding of the particularities of eighteenth-century prose narrative esthetics, this analysis of the Abbé Prévost’s Voyages de Robert Lade uses the lens of intertextuality to examine the role of “pseudoworks,” or texts that present themselves as independent works within another work.